A history of the Brethren movement its origins, its worldwide development and its significance for the present day - Coad, F. Roy, 1925- (Exeter, UK Paternoster, 1968)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Coad, F. Roy -- 1925- -- Brethren movement -- authors; Brethren movement -- church history